The iron chelator deferasirox synergises with chemotherapy to treat triple‐negative breast cancers. Issue 1 (7th August 2018) - Tury, Sandrine; Assayag, Franck; Bonin, Florian; Chateau‐Joubert, Sophie; Servely, Jean‐Luc; Vacher, Sophie; Becette, Véronique; Caly, Martial; Rapinat, Audrey; Gentien, David; de la Grange, Pierre; Schnitzler, Anne; et al.
Abstract: To ensure their high proliferation rate, tumor cells have an iron metabolic disorder causing them to have increased iron needs, making them more susceptible to iron deprivation. This vulnerability could be a therapeutic target. In breast cancers, the development of new therapeutic approaches is urgently needed for patients with triple‐negative tumors, which frequently relapse after chemotherapy and suffer from a lack of targeted therapies. In this study, we demonstrated that deferasirox (DFX) synergises with standard chemotherapeutic agents such as doxorubicin, cisplatin and carboplatin to inhibit cell proliferation and induce apoptosis and autophagy in triple‐negative breast cancer (TNBC) cells. Moreover, the combination of DFX with doxorubicin and cyclophosphamide delayed recurrences in breast cancer patient‐derived xenografts without increasing the side‐effects of chemotherapies alone or altering the global iron storage of mice. Antitumor synergy of DFX and doxorubicin seems to involve downregulation of the phosphoinositide 3‐kinase and nuclear factor‐κB pathways. Iron deprivation in combination with chemotherapy could thus help to improve the effectiveness of chemotherapy in TNBC patients without increasing toxicity. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.